Exact solutions of the nonlocal Gerdjikov-Ivanov equation. (31st August 2021) - Li, Miao; Zhang, Yi; Ye, Rusuo; Lou, Yu
Abstract: The nonlocal nonlinear Gerdjikov-Ivanov (GI) equation is one of the most important integrable equations, which can be reduced from the third generic deformation of the derivative nonlinear Schrödinger equation. The Darboux transformation is a successful method in solving many nonlocal equations with the help of symbolic computation. As applications, we obtain the bright-dark soliton, breather, rogue wave, kink, W -shaped soliton and periodic solutions of the nonlocal GI equation by constructing its 2 n -fold Darboux transformation. These solutions show rich wave structures for selections of different parameters. In all these instances we practically show that these solutions have different properties than the ones for local case.